Biosynthetic gene clusters and the evolution of fungal chemodiversity. Issue 7 (3rd January 2020) - Rokas, Antonis; Mead, Matthew E.; Steenwyk, Jacob L.; Raja, Huzefa A.; Oberlies, Nicholas H.
Abstract : This highlight synthesizes knowledge of the molecular evolutionary processes – functional divergence, horizontal transfer, and de novo assembly – that govern biosynthetic gene cluster diversification and the generation of chemodiversity in fungi. Abstract : Covering: up to 2019 Fungi produce a remarkable diversity of secondary metabolites: small, bioactive molecules not required for growth but which are essential to their ecological interactions with other organisms. Genes that participate in the same secondary metabolic pathway typically reside next to each other in fungal genomes and form biosynthetic gene clusters (BGCs). By synthesizing state-of-the-art knowledge on the evolution of BGCs in fungi, we propose that fungal chemodiversity stems from three molecular evolutionary processes involving BGCs: functional divergence, horizontal transfer, and de novo assembly. We provide examples of how these processes have contributed to the generation of fungal chemodiversity, discuss their relative importance, and outline major, outstanding questions in the field.